What matters to infrequent customers: a pragmatic approach to understanding perceived value and intention to revisit trendy coffe café - Ting, Hiram; Ramayah, T. (Springer, 2016)
Notwithstanding the rise of trendy coffe café, little is done to investigate revisit intention towards the café in the context of developing markets. In particular, there is a lack of study which provides theoretical and practical explanation to the perceptions and behaviours of infrequent customers. Hence, the study aims to look into the subject matter by using the theory of reasoned action and social exchange theory as the underpinning basis. The framework proposed by Pine and Gilmore (Strat Leadersh 28:18–23, 2000), which asserts the importance of product quality, service quality and experience quality in a progressive manner, is used to decompose perceived value in the model so as to determine their effcts on intention to revisit the café. Given the importance to gain practical insights into revisit intention of infrequent customers, pragmatism stance is assumed. Explanatory sequential mixed-method design is thus adopted whereby qualitative approach is used to confim and complement quantitative fidings. Self-administered questionnaire-based survey is fist administered before personal interview is carried out at various cafés. Partial least squares structural equation modelling and content analysis are appropriated successively. In the quantitative fidings, although product quality, service quality and experience quality are found to have positive effct on perceived value and revisit intention towards trendy coffe café, experience quality is found to have the greater effct than the others among the infrequent customers. The qualitative fidings not only confim their importance, but most importantly explain the favourable impressions they have at trendy coffe café based on their last in-store experience. While product and service quality might not necessary stimulate them to revisit trendy coffe café, experience quality driven by purposes of visit would likely affct their intention to revisit. As retaining customers is of utmost importance to businesses, and infrequent customers more than often make up the majority of the customers, the study provides meaningful and practical understanding of revisit intention.